PERFORMANCE OF ACTIVATED CARBON FROM WATER CHESTNUT (ELEOCHARIS DULCIS) as Fe ADSORBENT - Safitri, Maya; Haryanti, Ninis Hadi; Suryajaya, Suryajaya; Husain, Sadang (Indonesian Physical Review, 2025)
This research aims to investigate the performance of activated carbon from water chestnut (WC) as an Fe adsorbent on river water samples in South Kalimantan. The WC was carbonized at a temperature of 400 °C. Then the carbon was activated with two types of activators, KOH and H2SO4 solutions. The carbonization and the activation time were also varied in two different times, 1 and 2 hours. The electrical conductivity of Martapura River water was measured to investigate its condition or quality, and yielded about 0.56   or 5600 µS/cm. It is quite large compared to the standard 1000 µS/cm. After activated carbon treatment, the electrical conductivity is reduced by about 6.67 – 13.81%. For Fe adsorption, the reduction efficiency and adsorption capacity were in the range of 7.73 % – 22.94 % and 0.50 – 1.47 mg/g. The results showed that the prepared activated carbon is effective in adsorption and decreases the Fe metal content at room temperature.